A coalgebraic semantic framework for component-based development in UML - Sun Meng (2005)
This paper introduces a generic semantic framework for component-based development, expressed in the unified modelling language UML. The principles of a coalgebraic semantics for class, object and statechart diagrams as well as for use cases, are developed. It is also discussed how to formalize the refinement steps in the development process based upon a suitable notion of behavior refinement. In this way, a formal basis for component-based development in UML is studied, which allows the construction of more complex and specific systems from independent components.